HUBUNGAN LAMANYA PEMBERIAN MAGNESIUM SULFATE PADA PASIEN PEB DAN EKLAMPSIA DENGAN KEJADIAN HIPERMAGNESIUM DI RSUP DR. M. DJAMIL PADANG - Mayuliani, Mayuliani; Djanas, Dovy (Fakultas Kedokteran Universitas Andalas, 2018)
Objective :To find out the relationship between the duration of MgS04 administration in severe preeclampsia patients and eclampsia with the incidence of hypermagnesium.Method :This study is a comparative observational study using a cross sectional study design. The study was conducted in the medical record of Dr.M.Djamil Padang Hospital during the period January 1, 2016 to August 31, 2017 of pregnant women with severe preeclampsia and eclampsia, found 30 study subjects who met the inclusion criteria. Furthermore, data is recorded in a research form that has been provided, then carried out research data processing. Statistical analysis to assess significance using the chi-square test.Results : Magnesium levels increased in pregnant women with severe preeclampsia and eclampsia by 21 correspondents. Increased Magnesium levels in patients with severe preeclampsia and eclampsia who received MgS04 treatment for 48 hours by 16 correspondents (84.2%) and 5 correspondents with MgS04 administration for 24 hours.Conclusion : There is a significant relationship between the duration of Magnesium Sulfate with the incidence of hyperpermagnesium in patients with severe preeclampsia and eclampsia.Â Keywords: severe preeclampsia, eclampsia, magnesium sulfate, magnesium levels